Artificial Intelligence and Labor Markets: Analyzing Job Displacement and Creation - Maria, Siti; Purwinahyu, Purwinahyu; Fitriansyah, Fitriansyah; Rachmawaty, Arvita; Aini, Rohana Nur (Malikussaleh University, Aceh, Indonesia, 2025)
Artificial Intelligence (AI) is transforming labour markets through automation, job displacement, and the creation of new employment opportunities. This study employs a descriptive and comparative research design to analyze AI's impact across various industries, using statistical trend analysis, comparative sector evaluations, and qualitative NVivo-style interview analysis. Findings indicate that industries such as manufacturing and retail experience high job displacement rates (45% and 35%), whereas healthcare and Education show higher AI-driven job creation (50% and 60%). A major challenge identified is the AI skills gap, where 84% of interview respondents highlighted difficulties in workforce adaptation due to the lack of AI-related training programs. The trend analysis reveals a 55% increase in AI job creation between 2015-2025, but many workers remain unprepared for these new roles. Comparative industry analysis suggests that countries and sectors investing in reskilling initiatives and AI governance policies experience lower AI-induced unemployment rates. Beyond economic concerns, this study highlights AI's psychological and social implications in the workplace, such as job insecurity, workplace surveillance, and mental health challenges. To address these issues, governments and corporations must implement AI workforce reskilling programs, fair labour policies, and ethical AI deployment strategies. The research concludes that proactive AI governance and workforce adaptation strategies are essential for ensuring an inclusive and sustainable labour market transition.